THE DEFINITION AND MEASUREMENT OF INCOME. - Bangs, Robert B. (The Accounting Review, 1940)
The article focuses on the definition and measurement of income. There has long been need for a greater degree of agreement among economists, accountants and statisticians regarding problems of defining and measuring income. Although some differences are probably inevitable, because of various problems in the three fields, the amount of overlapping of subject matter is large and a common approach would add clarity to each discipline as well as strengthening the interrelationships between them. The accountant is interested primarily in the business unit and his chief function may be held to be the accurate measurement of periodic income as it accrues to the firm. As is well known, complete accuracy in the measurement of business income may be realized only upon the expiration of the firm's life, at which time the entire income, for the whole life of the enterprise, may be determined without error, assuming complete and accurate accounting records. But the practical problem is that of measuring the income of a going concern for short periods with speed, precision, and minimum expense. The economist may be led to the problem of defining income by many paths.